Study of The Physiological Status of Horses Before and After Training in Anantya Riding Club - Henny Endah Anggraeni; Igal Muhammad (Universitas Airlangga, 2024)
Background: The physiological status of a horse is an indicator of its health. Parameters that can be used to determine the health status of a horse include respiratory rate, heart rate, and body temperature. As the activity of a horse increases, its respiratory rate increases. By measuring respiratory rate, heart rate, and body temperature before and after training, changes in the physiological status of a horse can be determined. Purpose: This study aims to provide an overview of the physiological status of horses before and after training at Anantya Riding Club. Case: Physiological status of horses before and after training. Case Management: This study used a qualitative approach. Data on the physiological conditions of horses were collected before and after training. A digital thermometer was used to measure body temperature. A stethoscope was used to measure heart rate. Respiratory rate was measured by placing the back of the hand or the palm of the hand close to the horse's nose to feel its breath. These measurements were taken before and after training. Conclusion: This study concluded that the physiological status of horses after training showed an improvement. The average body temperatures of the horses before and after training were [37.6 ± 0.09]°C and [38.61 ± 0.03] °C, respectively. The average heart rates of the horses before and after training were 41.0 ± 2.4 beats/minute and 90.2 ± 3.5 beats/minute, respectively. Finally, the average respiratory rates of the horses before and after training exercise were 39.7 ± 3.0 breaths/minute and 101.2 ± 0.5 breaths/minute, respectively.